Social media use by frontline government agencies review and recommendations - David, Clarissa C.
This paper reports on three case studies conducted to systematically examine how frontline government social services use social media and how their practices might be improved to optimize engagement with the public to serve agency goals, and to investigate the organizational setting around social media management within the agencies. The three cases involve the Department of Education (DepEd), the Department of Health (DOH), and the Home Mutual Development Fund (HMDF). The results indicate that there is a wide variety of approaches to social media, from a closed and outsourced system where materials posted go through layers of high-level approval to open and internal systems with greater autonomy in content development. Social media are now considered necessary parts of communication strategies, but how each agency adopts them tends to differ. Considering that these are official government social media accounts, there is a very high level of engagement with audiences for some of the agencies. The paper then makes recommendations on policies, on organizational arrangements, and on integration into broad overall digital and communication strategies of frontline government agencies.
Keywords: Social media; Facebook; Government communication; Public communication